Ambivalensi Hukum Wasiat Wajibah Atas Anak Angkat (Paradoksial KHI dan Sistem Hukum Nasional dalam Prinsip Keadilan Wasiat Wajibah) - Uzlah Wahidah (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2024)
An adopted child is someone else's child who is officially considered their own child by the adoptive parents according to local customary law, because the aim is for the continuity of offspring and/or maintenance of household assets. In Law Number 23 of 2002 concerning Child Protection, it is stated that an adopted child is a child whose rights are transferred from the area of authority of the family of parents, legal guardians, or other people responsible for the care, education and raising of the child, into the local environment. adoptive parents' family based on a court decision or order. This research aims to find out the nature of the determination of the mandatory part of the will for adopted children, and to find that the principle of justice in the mandatory will for children has been fulfilled in the KHI. The method used in this research is qualitative with a type of library research using data content analysis methods. The results of the research show that the law on the inheritance rights of adopted children in wills is mandatory in Islam. The scholars have different opinions regarding the permissibility of bequests to adopted children, both adherents of the principle of bilateral inheritance and adherents of the patrilineal school of thought and law. Meanwhile, the principle of justice in obligatory wills for adopted children from the assets inherited from their adoptive parents, Indonesian law provides protection through Article 209 of the Compilation of Islamic Law.